Pleomorphic Adenoma of the Upper Lip: A Case Report - KC, Anjana; Shrestha, Brijesh; Paudel, Vikash (Med Phoenix, 2022)
Pleomorphic adenoma is the most common benign tumour of the major salivary gland presenting as a painless mass gradually increasing in size, usually involving the parotid gland. In the minor salivary gland, it is more common in the palate. Pleomorphic adenoma of the lip is a rare tumour. Thus, we present a case of pleomorphic adenoma originating from the upper lip in a 75 years old male patient. The tumor was completely excised and sent for histopathological examination which showed the microscopic features of pleomorphic adenoma to confirm the diagnosis.